Review of the Inclusiveness of the 2019 Simultaneous General Election Stages in Yogyakarta City - Pangky Febriantanto (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
The stages of the 2019 Simultaneous General Election have been completed, and one of its main objectives was to evaluate the inclusiveness aspects that accommodate people with disabilities. This study used a qualitative research method with a field observation approach supported by desk research to obtain accurate data. Several stages that can be reviewed to measure inclusiveness include the Stage of Establishment of the Organizing Body, the Stage of Socialization, the Stage of Updating Voter Data, the Stage of Voting and Counting Votes, the Stage of Nomination, the Stage of Campaign, and the Stage of Recapitulation or Determination of Election Results. Based on the results of the study, the stages that have supported inclusivity well include the Stage of Establishment of the Organizing Body, the Stage of Socialization, the Stage of Updating Voter Data, and the Stage of Voting and Counting Votes. However, several stages that still do not support inclusivity are the Nomination, Campaign, and Recapitulation or Determination of Election Results Stages, which require more attention to improve accessibility for people with disabilities, especially in terms of more easily accessible information and more adequate facilities.